Improving the Health of the Nation Through Transdisciplinary Community Engagement - Roger A. Rennekamp (The University of Alabama, 2022)
This article chronicles how three land-grant universities and one non-land-grant university medical center have transformed to meet the needs of people where they live, work, learn, and play. In this article, we first get a glimpse of how an institutional commitment to community engagement and supportive administrative structures are advancing community-based public health practice at Oregon State University. Next, we learn how Texas A&M's AgriLife Extension Service is using community data to focus on the most pressing needs of the state's 254 counties. We then examine how Mississippi State University is working to address the shortage of health care professionals in its state by introducing young people to health careers and encouraging medical students to practice in the state. Finally, we learn how the University of New Mexico Medical Center and New Mexico State University are using the tried-and-true principles of cooperative extension to address the state population's health needs through Health Extension Rural Offices.